Nordic guidelines 2014 for diagnosis and treatment of gastroenteropancreatic neuroendocrine neoplasms. (October 2014) - Janson, Eva Tiensuu; Sorbye, Halfdan; Welin, Staffan; Federspiel, Birgitte; Grønbæk, Henning; Hellman, Per; Ladekarl, Morten; Langer, Seppo W.; Mortensen, Jann; Schalin-Jäntti, Camilla; Sundin, Anders; Sundlöv, Anna; et al.
Abstract Background . The diagnostic work-up and treatment of patients with neuroendocrine neoplasms (NENs) has undergone major recent advances and new methods are currently introduced into the clinic. An update of the WHO classification has resulted in a new nomenclature dividing NENs into neuroendocrine tumours (NETs) including G1 (Ki67 index ≤ 2%) and G2 (Ki67 index 3–20%) tumours and neuroendocrine carcinomas (NECs) with Ki67 index > 20%, G3. Aim. These Nordic guidelines summarise the Nordic Neuroendocrine Tumour Group's current view on how to diagnose and treat NEN-patients and are meant to be useful in the daily practice for clinicians handling these patients.